Impact of COVID-19 Pandemic on the Incidence of Sexually Transmitted Infections in Northern Finland in 2019 to 2022 - Vesa Mäki-Koivisto; Suvi-Päivikki Sinikumpu; Jari Jokelainen; Elina Aho-Laukkanen; Ilkka S. Junttila; Laura Huilaja (Medical Journals Sweden, 2022)
The coronavirus SARS-CoV-2 (COVID-19) pandemic led to major restrictions in daily life and social contacts in Finland in March 2020. The effect of these restrictions on sexually transmitted infections (STIs) is unclear. The aim of this study was to analyse the incidence and positive rates of sexually transmitted infections in Northern Finland between 2020 and 2021 and compare these with the years prior to the pandemic. Numbers of positive Chlamydia trachomatis, HIV and hepatitis C samples were lower in 2020 to 2021 than in previous years, whereas more gonorrhoea and syphilis was found during pandemic than in previous years. The number of new cases of C. trachomatis reported each month decreased in the first months of the pandemic, but exceeded the prior pandemic-level in autumn 2020. When the mean positive sample rates were compared with the years 2015 to 2019, there was a significant decrease in positive C. trachomatis (p < 0.001) and hepatitis C (p < 0.001) sample rates in both 2020 and 2021. The positive rates for Treponema pallidum in 2020 did not differ significantly (p = 0.38) from previous years. In conclusion, these results show that sexually transmitted infections occurred despite recommendations for social distancing during the COVID-19 pandemic. Thus, easy access to STI testing should always be available, even during exceptional circumstances.